Analysis of the Implementation of Educational Quality Management in Senior High School in Pekanbaru - Ana Afifah Asri; Mualif Hari Wahyudi (Journal of English Language and Education, 2026)
Educational quality plays a significant role in enhancing educational services and developing competent graduates. Nevertheless, schools often encounter challenges in sustaining quality improvement initiatives and ensuring compliance with educational standards. This study aims to examine the implementation of educational quality management at Dharma Loka High School in Pekanbaru. A descriptive qualitative approach was employed, with data collected through interviews involving two informants, namely the vice principal for curriculum affairs and a teacher, as well as the analysis of school documents. The findings reveal that quality management has been implemented through the Merdeka Curriculum, the Internal Quality Assurance System (SPMI), academic supervision and evaluation, and several flagship programs. These efforts are reinforced by the school’s A accreditation status and Education Report results showing very good literacy and numeracy achievement. The findings emphasize the importance of integrating quality assurance, curriculum implementation, and school programs to achieve continuous educational quality improvement.